Functional Ag‐Exchanged Zeolites as Biocide Agents. Issue 17 (2nd May 2018) - Cerrillo, José Luis; Palomares, Antonio Eduardo; Rey, Fernando; Valencia, Susana; Pérez‐Gago, María Bernardita; Villamón, Diana; Palou, Lluís
Abstract: Materials based on silver are used for controlling different pathogenic microorganisms. However, the influence of the silver carrier in the biocidal activity of the material has been scarcely reported. The present research is focused on studying the influence of zeolite properties on the biocidal activity of silver‐exchanged zeolites, acting as reservoirs of silver species. The biocidal action of Ag‐Faujasite (Ag‐FAU) and Ag‐Linde Type A (Ag‐LTA) zeolites, containing different silver contents, is studied against different types of bacteria and fungi. Importantly, zeolite structure is found to be a significant parameter for controlling the antibacterial activity of Ag‐exchanged zeolites. The results show that Ag‐FAU presents a higher activity than Ag‐LTA, because the topology of FAU combined with its highest Si/Al ratio favors the formation and release of silver species with important biocidal activity. Some insights on the bactericidal mechanism of Ag‐zeolites are envisaged by means of high resolution transmission electron microscopy, showing the multi‐targeted biocidal action of Ag species released from zeolites. Besides, it is shown that Ag‐zeolites are more active against bacteria than fungi. Antifungal activity is highly dependent on the fungi species and the structure of the zeolite is not as determinant as it is for the antibacterial activity. Abstract : The battle against microorganisms using non‐toxic materials is a necessity nowadays. In this work, the bactericide and fungicide properties of diverse silver‐zeolites are investigated, and they are related to their physical‐chemical properties.